Molecular Detection of nan, tly and dsA gene of Propionibacterium acnes Isolated from acne vulgaris in Babylon Province - Rabab J H AL-Hasseny1 , Lamees A. Abdul-Lateef 2 , Hussein Abbas AL-Sultany3 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Propionibacterium acnes virulence factors can be divided into chromosomal, plasmid and bacteriophagesencoded virulence factors. Many of the Propionibacterium acnes virulence factors, are camp5, gehA, tly,sialidases, neuraminidases, endoglycoceramidases, lipases, and hemolysins genes are clustered in certainareas of the chromosome. A total of 200 clinical acne samples were collected during this study whichobtained from patient Suffering from acne vulgaris who to the out-patient clinics and delivery dermatologyunite of acne, in hospitals of Babylon Province: AL-Hashmeia general Hospital and Marjan hospital,during the period from April to November 2019. Out of 200 specimens 14 (7.7%)were detected by cultureand vitek2 compact9 (64.3%)of them were confirmed by PCR using target gene of Propionibacterium acnesPCR was conducted to determine the some virulence genes of the isolates by using primers nan, tly and dsAgene. The PCR amplification products were visualized by electrophoresis on 1% agarose gels for 35min at70v. The sizes of the amplicons were determined by comparison to the 200 bp allelic ladder. Among isolatesstudies it was found that nan gene present in 6/9(66.7%). isolates, dsA gene it was found in only 3isolates(33.4%) while tly gene it was found in all isolates(100%) .